Deciphering the introduction and transmission of SARS-CoV-2 in the Colombian Amazon Basin. - Nathalia Ballesteros; Marina Muñoz; Luz Helena Patiño; Carolina Hernández; Felipe González-Casabianca; Iván Carroll; Mauricio Santos-Vega; Jaime Cascante; Andrés Angel; Alejandro Feged-Rivadeneira; Mónica Palma-Cuero; Carolina Flórez; et al. (Public Library of Science (PLoS), 2021)
Background The SARS-CoV-2 pandemic has forced health authorities across the world to take important decisions to curtail its spread. Genomic epidemiology has emerged as a valuable tool to understand introductions and spread of the virus in a specific geographic location. Methodology/principal findings Here, we report the sequences of 59 SARS-CoV-2 samples from inhabitants of the Colombian Amazonas department. The viral genomes were distributed in two robust clusters within the distinct GISAID clades GH and G. Spatial-temporal analyses revealed two independent introductions of SARS-CoV-2 in the region, one around April 1, 2020 associated with a local transmission, and one around April 2, 2020 associated with other South American genomes (Uruguay and Brazil). We also identified ten lineages circulating in the Amazonas department including the P.1 variant of concern (VOC). Conclusions/significance This study represents the first genomic epidemiology investigation of SARS-CoV-2 in one of the territories with the highest report of indigenous communities of the country. Such findings are essential to decipher viral transmission, inform on global spread and to direct implementation of infection prevention and control measures for these vulnerable populations, especially, due to the recent circulation of one of the variants of concern (P.1) associated with major transmissibility and possible reinfections.